Comparative Analysis of Energy Efficiency in Organic and Conventional Farming Systems A Case Study of Black Carrot (Daucus carota L.) Production in Turkey - Celik, Yusuf; Peker, Kenan; Oguz, Cennet (2010)
This study compared the energy efficiency and cost/benefit ratio of conventional and organic farming systems for black carrot (Daucus carota L.) in Konya province, Turkey. In the research, energy consumption for different farm operations from land preparation to transportation was considered. The farms were selected through stratified random sampling. Data were collected through field survey of 56 respondents in carrot farms during production periods in 2007-2008. Black carrot production was considered for the study as it is a very good source of colored food. Therefore, black carrot production must take into consideration the requirements for eco-design requirements and energy labeling. Based on the results, increasing amount of inputs was more effectively used in the organic farming system compared with the conventional system. Total energy requirement under conventional farming was 75,335.72 MJ ha -1 and 37,758.82 MJ ha -1 for organic farming. There was higher demand for energy in conventional farming (49.88%) than organic farming. On the other hand, the need for labor per hectare was higher for organic farming than for the conventional farming system. The energy output-input ratios for conventional and organic farming systems were 1.30 and 1.90, respectively. Moreover, the benefit-cost ratios were 1.83 and 2.05, respectively. Energy efficiency in the organic systems may increase by 1.32 kg ha -1 and by 0.23 kg ha -1 in the conventional systems.
Keywords: Carrots; Agricultural systems